2003
DOI: 10.1007/s00436-003-0963-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasite infections on a national scale among primary schoolchildren in Laos

Abstract: In order to investigate the epidemiological situation of intestinal parasite infections in Laos, parasitological surveys were carried out on a national scale including 17 provinces and the Vientiane Municipality. A total of 29,846 stool specimens were collected from primary schoolchildren from May 2000 to June 2002 and examined once with the cellophane thick smear technique. The cumulative egg positive rate for intestinal helminths was 61.9%. By species, the rate for Ascaris lumbricoides was 34.9%, hookworm 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 7 publications
10
115
12
Order By: Relevance
“…This finding confirms the previous reports by Rim et al (2003) in the same province and by Kobayashi et al (2000), who showed high infection rates in the neighbouring Khammouane province. In addition, our study is most likely to underestimate infection rates.…”
Section: Prevalence and Impact Of Opisthorchis Viverrinisupporting
confidence: 93%
See 2 more Smart Citations
“…This finding confirms the previous reports by Rim et al (2003) in the same province and by Kobayashi et al (2000), who showed high infection rates in the neighbouring Khammouane province. In addition, our study is most likely to underestimate infection rates.…”
Section: Prevalence and Impact Of Opisthorchis Viverrinisupporting
confidence: 93%
“…The survey was conducted in the Saravane district, province of Saravane, southern Lao PDR (Figure 1), where recently a high prevalence of O. viverrini was found among schoolchildren (Rim et al, 2003). The province has a population of approximately 318 100; 20% are children under 5 years of age.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that O. viverrini is endemic in all provinces of Lao PDR. 7 The highest prevalence rates were found in central and southern parts, reaching levels of up to 60%. 8 However, in these studies only 'Opisthorchis-like' eggs were reported.…”
Section: Introductionmentioning
confidence: 96%
“…viverrini infection is endemic in several countries in Southeast Asia and in all provinces of Laos (Rim et al, 2003). It is highly prevalent in central and southern Laos, reaching infection rates of more than 90% in adult populations (Forrer et al, 2012;Sayasone et al, 2007;Sayasone et al, 2011).…”
Section: Introductionmentioning
confidence: 99%